Research and improvement of precise angle control system - Sigitas Šakalinis (Mokslas: Lietuvos Ateitis, 2010)
The main task was investigation and precision improvement for a positioning drive, installed in a test rig for testing and calibration of the geodetic instruments at Vilnius Gediminas Technical University, Institute of Geodesy. Replacement of a stepper motor and a microstepping controller design increased positioning accuracy to 0.1''. Vibrations and noise of the test rig were significantly decreased using an optimized control algorithm, where resonating step frequencies were bypassed. The time of scale rotation between measurements (every 30°) achieved less than 1.5 min. Methods of the further precision improvement were selected, and this research is in progress now.